Effect of Acclimation Temperature on Infection of Alfalfa by Ditylenchus dipsaci - Griffin, G D (Journal of nematology, 1974)
Ditylenchus dipsaci showed an affinity, in relation to infection, for the temp at which it had been acclimated. The optimum infective temp was also correlated with field temp when collections were made during different seasons and from climatically different geographical areas. Nematode developmental stage did not influence infectivity